2022
DOI: 10.1155/2022/2203065
|View full text |Cite|
|
Sign up to set email alerts
|

The Diagnostic Value of Scanning in the Injury of Triceps Crus of Volleyball Players

Abstract: The study goal is to solve the problem of the diagnosis of triceps crus injury of volleyball players, meet the needs of volleyball players and team doctors for the correct diagnosis of triceps crus injury scanning, make up for the deficiency that triceps crus injury scanning diagnosis is easy to make mistakes, and improve the efficiency and ability of triceps crus injury diagnosis scanning. Because the experiment involves the technical action of volleyball jump serve, DELSYSR Trignomobile wireless portable sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…According to Hu et al (2022), the degree of a joint's flexibility determines how well it can carry out specific movements. Additionally, Zhao & Liu (2022) stated an athlete's speed, strength, and explosive power can all be improved to various degrees by training flexibility. Flexibility is therefore required when blocking and striking the ball.…”
Section: Introductionmentioning
confidence: 99%
“…According to Hu et al (2022), the degree of a joint's flexibility determines how well it can carry out specific movements. Additionally, Zhao & Liu (2022) stated an athlete's speed, strength, and explosive power can all be improved to various degrees by training flexibility. Flexibility is therefore required when blocking and striking the ball.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%